Sikap Toleransi Beragama Siswa Madrasah Aliyah di Kabupaten Kendal Jawa Tengah - Nugroho Eko Atmanto; Umi Muzayanah (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Madrasah is a formal educational institution that provides education with the uniqueness of the Islamic religion. The condition of the madrasah environment, which is homogeneous and monoculture in terms of religion, impacts student attitudes concerning religious believers' relationship. The interactions that occur in the madrasah environment almost always involve social structures that tend to be homogeneous. This study examines the scholars' tolerance to religious believers' relationship among Madrasah Aliyah students in Kendal Regency. This study uses a quantitative approach with data collection methods through questionnaires. The results showed that most of the students of Madrasah Aliyah in Kendal (74.15%) had an attitude of tolerance among religious believers in the